Effect of imperfections on and modelling of conductivity and hardness of high-Zn X7xxx cast al-alloys produced from recycled beverage can - Kazeem, Abubakar; Job Ajala, Amkpa; Badarulzaman, Nur Azam; Wan Ali, Wan Fahmin Faiz (Penerbit UTHM, 2020)
In this paper, the effect of imperfections as a result of formation of new phases on electrical and macro hardness property of a novel experimental high-Zn Al-Zn-Mg-Cu alloys produced from recycled beverage can was investigated with the aim of correlating hardness with conductivity using ANOVA. Alloys were observed in the As Cast (AC), annealed (O), natural aged (T4) and artificial aged (T6) conditions. Heat treatments supported the formation of hardening precipitates like the Al2.06Fe4, α-AlFeSi, Al7Cu2Fe, θ(Al2Cu), β-AlFeSi and MgZn2 phases. Imperfections inform of voids and contaminants are by-products of recycled aluminium and casting route. Peak obtainable hardness of 122.94 HV in the T6 condition was observed in an alloy of Al-5.0 Zn-1.5 Mg- 0.35 Cu. The same alloy’s conductivity is 3.676  107 S/m. The least hardness of 38.16 HV and conductivity of 3.533  107 S/m is credited to an alloy of Al- 5.0 Zn-1.00 Mg-0.35 Cu in the O condition. The relationship between hardness and conductivity is nonlinear. Models developed to predict the hardness of this experimental alloys fits all the variables and covers the AC, O, T4 and T6 respectively. The need for further investigation on the imperfections, optimization of mechanical properties and additional mechanical properties investigation is required.